Analysis of Item Difficulty Index for Midterm Examinations in Junior High Schools 5 Bengkulu City - Rapita Pratiwi; septia reflianti; Sura Antini; Ahmad Walid (Asian Journal of Science Education, 2021)
This study aims to analyze the difficulty level of the IPA UTS items for Class VII and VIII at SMP Negeri 5 Bengkulu City. This study used a qualitative descriptive research design. The instrument used in this study was the text of the Middle Semester Test (UTS) for the Middle School Science Subject for the in Junior High School. The data collected were analyzed using the Difficulty Index formulation. The results showed that the analysis of the difficulty level of the IPA UTS items for Class VII and VII at SMP Negeri 5 Bengkulu City for the academic year 2018/2019 had a difficult question category in grade VII of only 10%, easy question category 15%, and question category which is being 75%. Likewise, Class VIII has only 5% difficult question categories, 10% easy question categories, and 85% medium question categories. This indicates that the quality of the UTS questions is very good.